Treatment of rhegmatogenous retinal detachment: from the past to the future (Ukrainian Journal of Ophthalmology, 2025)
Rhegmatogenous retinal detachment (RRD) is a severe disorder that can potentially lead to blindness. The traction developing in pathological attachment of the vitreous to retinal degeneration areas and in posterior hyaloid detachment leads to formation of retinal breaks and subsequent retinal detachment. The approach to treatment of RRD has changed with years from cautery (J. Gonin, 1920) to modern vitrectomy (R. Machemer, 1973). Current advances in vitrectomy are related mostly to the three major fields: development of advanced vitrectomy tools, novel operative techniques and tamponade agents. The tamponade agents used in vitrectomy have specific advantages and disadvantages. Therefore, new solutions are being sought to minimize harmful effects of tamponade agents on ocular tissues, which would make the process of rehabilitation more comfortable for patients. In recent decades, the potential for using hydrogels as a substitute to the vitreous removed during vitrectomy has been actively explored (Widder, 1960, Balazs, 1972, Malson, 1985). The first commercially available biomedical sodium hyaluronate product for use in eye surgery, Healon, was developed by Balazs. Although Healon was developed as a vitreous substitute, it has been successfully used also in cataract surgery, and truly initiated the age of viscosurgery. The research on the potential for using hydrogels as a visual substitute is underway.
Keywords: vitrectomy; silicone oil; gas tamponade; rhegmatogenous retinal detachment; hydrogel; viscosurgery